Forgetting in early modern English literature and culture : Lethe's legacies - Ivic, Christopher, 1968-; Williams, Grant, 1965- (London ; New York : Routledge, 2004)
Opening up an area overlooked by Renaissance scholarship, this collection of essays historicizes and theorizes 'forgetting' in English literary texts.
Book Cover; Title; Contents; List of figures; List of contributors; Acknowledgments; Introduction: sites of forgetting in early modern English literature and culture; The decay of memory; Lethargic corporeality on and off the early modern stage; Pleasure's oblivion: displacements of generation in Spenser's Faerie Queene; Signs; Textual crudities in Robert Burton's Anatomy of Melancholy and Thomas Browne's Pseudodoxia Epidemica; Off the subject: early modern poets on rhyme, distraction, and forgetfulness; Narratives; Reassuring fratricide in 1 Henry IV.
Includes bibliographical references (pages 179-192) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism; Memory in literature; Mémoire dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Memory in literature; English literature -- Early modern, 1500-1700 -- History and criticism; English literature -- Early modern; Memory in literature; 1500-1700; Criticism, interpretation, etc